Study on Magnetohydrodynamics Cu-water Nanofluid Flow with Different Shapes of Nanoparticles in a Divergent Channel - Alam, Md Sarwar; Yasmin, Suraiya; Das, Ashik Chandra (GANIT: Journal of Bangladesh Mathematical Society, 2022)
This paper studies the two-dimensional magnetohydrodynamics steady incompressible Cu-water nanofluid flow considering different shapes of nanoparticles in a divergent channel. The continuity equation, momentum equations and energy equation governing the problem are transformed to a set of non-dimensional ordinary differential equations by suitable transformations. The transformed dimensionless equations are solved by using power series approach and then Hermite-Padé approximation method is applied for analyzing the solution. Brick, cylinder and platelet-shaped Cu-nanoparticles are considered to investigate the effect of shape factor. Moreover, impact of physical parameters such as channel angle, flow Reynolds number, Hartmann number, Eckert number, Prandtl number and nanoparticles solid volume fraction on velocity and temperature profiles are also examined. The results show that the different shapes of Cu-nanoparticles have significant effect on the temperature distributions in the channel. GANITJ. Bangladesh Math. Soc.41.2 (2021) 41-52